Activation of calcitonin gene-related peptide signaling through the prostaglandin E2-EP1/EP2/EP4 receptor pathway in synovium of knee osteoarthritis patients - Minatani, Atsushi (J Orthop Surg Res, 2016)
BACKGROUND: Calcitonin gene-related peptide (CGRP) is a 37-amino-acid vasodilatory neuropeptide that binds to receptor activity-modifying protein 1 (RAMP1) and the calcitonin receptor-like receptor (CLR). Clinical and preclinical evidence suggests that CGRP is associated with hip and knee joint pain; however, the regulation mechanisms of CGRP/CGRP receptor signaling in synovial tissue are not fully understood. METHODS: Synovial tissues were harvested from 43 participants with radiographic knee osteoarthritis (OA; unilateral Kellgren/Lawrence (K/L) grades 3–4) during total knee arthroplasty. Correlationships between the mRNA expression levels of CGRP and those of tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, and cycloxygenase-2 (COX-2) were evaluated using real-time PCR analysis of total RNA extracted from the collected synovial tissues. To investigate the factors controlling the regulation of CGRP and CGRP receptor expression, cultured synovial cells were stimulated with TNF-α, IL-1β, IL-6, and prostaglandin E2 (PGE2) and were also treated with PGE2 receptor (EP) agonist. RESULTS: CGRP and COX-2 localized in the synovial lining layer. Expression of COX-2 positively correlated with CGRP mRNA expression in the synovial tissue of OA patients. The gene expression of CGRP and RAMP1 increased significantly in synovial cells exogenously treated with PGE2 compared to untreated control cells. In cultured synovial cells, CGRP gene expression increased significantly following EP4 agonist treatment, whereas RAMP1 gene expression increased significantly in the presence of exogenously added EP1 and EP2 agonists. CONCLUSIONS: PGE2 appears to regulate CGRP/CGRP receptor signaling through the EP receptor in the synovium of knee OA patients.